Implementasi Teknologi Digital di Sekolah Dasar Negeri Tulungrejo 1 Pada Kelas IV Bojonegoro - Widyana Nurfajar Isnaeni; Humairah Fauziah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
The use of digital technology in basic education is increasingly becoming the main focus in efforts to improve the quality of learning. This research aims to determine the implementation of digital technology at Tulungrejo 1 Elementary School in class IV in Bojonegoro. The main focus of this research is whether digital technology has been implemented in this elementary school. This includes teachers' perceptions and experiences in using digital technology, as well as its impact on student learning. The research method used is qualitative. Data was collected through in-depth interviews with fourth grade teachers, direct classroom observations, and analysis of related documents. The research results show that the implementation of digital technology has had a positive impact in improving the quality of learning at SDN Tulungrejo 1. However, the challenges faced include the availability of adequate technological infrastructure and the readiness of teachers to integrate technology in the curriculum. This study provides recommendations for increasing teacher training in the use of technology, improving technology infrastructure, and school development policies that support the effective use of digital technology in learning.